2003
DOI: 10.2460/ajvr.2003.64.1482
|View full text |Cite
|
Sign up to set email alerts
|

Changes in heart rate variability in horses during immersion in warm springwater

Abstract: Increases in HF power indicates that the parasympathetic nervous activity in horses increases during immersion in warm springwater. Thus, immersion in warm springwater may provide a means of relaxation for horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Methodological issues reported by Stucke et al [30] also highlighted the movement of horses while measuring RR-intervals and the fact that RRinterval series recorded should be longer than the actual 5-minute tachogram that is used for HRV quantification. This longer interval series is recommended due to a relatively high incidence of first and second degree AV-blocks as well as other arrhythmias in resting horses in response to dominant vagal activity [32]. Automatic assumption of the applicability of methodology used in human or other animal studies during HRV quantification in horses may provide an explanation for the low comparability between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Methodological issues reported by Stucke et al [30] also highlighted the movement of horses while measuring RR-intervals and the fact that RRinterval series recorded should be longer than the actual 5-minute tachogram that is used for HRV quantification. This longer interval series is recommended due to a relatively high incidence of first and second degree AV-blocks as well as other arrhythmias in resting horses in response to dominant vagal activity [32]. Automatic assumption of the applicability of methodology used in human or other animal studies during HRV quantification in horses may provide an explanation for the low comparability between studies.…”
Section: Introductionmentioning
confidence: 99%
“…It may be suggested that in horses that participate in races, stress responses increase progressively up to a point at which the body becomes unable to manage them. As reported by Kato et al (2003), enhanced parasympathetic system activity reflects a state of physical and mental relaxation. It exerts a trophotropic effect on the regeneration processes by inhibiting utlization of matter and energy (Baselli et al 1987;Gill 2003).…”
mentioning
confidence: 69%
“…Sinus arrhythmias and atrioventricular (AV) blocks of first and second degree are considered to be physiological in resting horses, due to a dominant vagal activity (Kato et al, 2003). In short term HRV measurements, AV-blocks occur in a quarter (Oel et al, 2010) to a third (Rietmann et al, 2004a) of horses that are resting.…”
Section: Methodological and Technical Issuesmentioning
confidence: 99%
“…Rietmann et al (2004b) and Witte (2001) defined their own thresholds with human-derived algorithms (Bernasconi et al, 1998) based on counted respiratory frequency. Individual frequency band thresholds vary as a function of current physiological condition (von Borell et al, 2007) and frequency-band thresholds Kuwahara et al (1996) LF >0.01-0.07 Hz HF >0.07-0.6 Hz Hada et al (2006), Hoffmann (2008, Kato et al (2003), Kuwahara et al (1998Kuwahara et al ( , 1999, Marchant-Forde (2003), Matsuura et al (2010), Minero et al (2006), Oel et al (2010Oel et al ( , 2014, Ohmura et al (2001Ohmura et al ( , 2006aOhmura et al ( ,b, 2012a, Physick-Sheard et al (2000), Uhlendorf (2009) should not be defined without pharmacological blockade of the ANS (Marchant-Forde, 2003), because these defined frequency bands combine individual variations.…”
Section: Frequency Band Thresholds In Horsesmentioning
confidence: 98%